Implementation of Sustained Mindfulness Training to Reduce Stress Levels and Improve the Social-Emotional Competence of Teachers at SD Negeri Mlarangan - Niken Dwi Astuti; Rahmat Mulyono; Jumintono (Universitas Pakuan, 2026)
High levels of work-related stress among elementary school teachers negatively affect the quality of learning and interpersonal relationships within the school environment. This school action research aimed to examine the effectiveness of sustained mindfulness training in reducing stress levels and improving the social-emotional competence of teachers at SD Negeri Mlarangan. The study was conducted in two cycles involving 10 teachers as research subjects. The instruments used included the Teacher Work Stress Scale, the Social-Emotional Competence Scale, observation sheets, and reflective journals. Data were analyzed descriptively using quantitative and qualitative approaches. The findings revealed that the implementation of sustained mindfulness training over eight weeks successfully reduced the average teacher stress score from the high category (76.4) to the low category (42.3), while social-emotional competence increased from 58.2% to 84.7%. The most significant improvement occurred in the dimensions of self-awareness and emotional management. This study concludes that sustained mindfulness training is an effective and applicable intervention for improving the mental health and social-emotional competence of elementary school teachers.